X-ray powder diffraction study of the stability of clathrate hydrates in the presence of salts with relevance to the Martian cryosphere. (15th January 2019) - Safi, Emmal; Thompson, Stephen P.; Evans, Aneurin; Day, Sarah J.; Murray, Claire A.; Baker, Annabelle R.; Oliveira, Joana M.; van Loon, Jacco Th.
Abstract: Water on the present day Martian surface is thought to exist in two thermally distinct sub-surface reservoirs: as ice in the cryosphere and as groundwater located deeper in the crust. These sub-surface environments are thought to contain saline, rather than pure, water and laboratory studies on whether or not clathrate hydrates can form in such environments are lacking. We fill this gap by performing synchrotron radiation X-ray powder diffraction to investigate the formation and evolution of clathrate hydrates in weak chloride solutions at CO2 pressures, and over temperature ranges, that are similar to those found in the Martian regolith. We have found that clathrate hydrates can form under conditions relevant to the Martian cryosphere, despite the presence of chloride salts. We find that the dissociation temperatures for CO2 clathrate hydrates formed in saline solutions are depressed by 10–20 K relative to those formed in pure water, depending on the nature of the salt and the CO2 pressure. We suggest that the inhibiting effect that salts such as MgCl2, CaCl2 and NaCl have on clathrate hydrate formation could also be related to the salts' effect on the formation of the low temperature phase of ice. However, despite the inhibiting effect of the salts, we conclude that the presence of clathrate hydrates should still be possible under conditions likely to exist within the Martian cryosphere.